O uso da contabilidade de custos nas empresas so setor industrial de derivados de polietileno no município de Teresina - Brito, Betina dos Santos (2008)
This study is investigating how the information generated is used by Contabibility of costs in the decision making process of enterprises in the industrial sector of derivatives of polyethylene in the city of Teresina. The industry represents a paper Piauiense relevant in the economy, since it is responsible for two thousand and seven-hundreds direct employees, averaged over the past five years (RAIS / MTE 2005). The branch of polyethylene derivatives groups today in the city of Teresina, more than thirty industries, with the possibility, even in the year 2008, increasing its productioning, generating more direct jobs. To carry out this research was used the technique of direct observation, interviews with the managers of each industry by implementing a structured interview. It was used as a support theoretical research-takings literature. As the problematization the study attempts to answer how the industries of polyethylene products in the city of Teresina use the information for its costs in the management process. Specific objectives have sought to ascertain the type of cost used in industries and investigate the composition of such costs. The work this structured into five chapters. The first shows the introduction, with the delimitation of the topic, reasons, goals and structure of work, in the second chapter is the theoretical reference, in the third brings the result of the search field, in the fifth, the final considerations. The results show that the industries use the accounting of costs in its so-management process to support the decision-making within the industry-produced additive, adding advantages in competitiveness and growth within their industry.